"I think we should pull together as a team"- Together on the path to the top: Interdisciplinary collaboration in partnership with women on long-term health after hypertensive disorder of pregnancy. (September 2022) - Roth, Heike; Morcos, Ms Veronica; Roberts, Lynne; Hanley, Mrs Lisa; Henry, Amanda; Homer, Caroline
Abstract : Background: Hypertensive disorders of pregnancy (HDP) affect 5-10% of pregnancies and significantly increase a woman's risk of developing cardiovascular disease, including 2-3 times the risk of heart attack, stroke and diabetes. Long-term risks rise within 10 years after HDP and continue lifelong, making long-term health after HDP of major public health importance. Prior findings suggest evidence to practice gaps in knowledge translation to women about their post-HDP health. Objective: To explore Australian women's and healthcare provider's (HCP) education and follow-up preferences regarding health after HDP. Focus will be drawn on the role of the midwife within this context. Methods: A qualitative study using a framework analysis was undertaken. Women with a history of HDP and HCP who previously completed a survey about long-term health after HDP were invited to participate. Interviews explored participant preferences and priorities concerning knowledge acquisition around long-term health after HDP. Findings: Thirteen women and twenty HCP (including 11 midwives) were interviewed. Women's preference included early post-HDP risk counselling about long-term and mitigable risk factors from their midwife/general practitioner/specialist, accompanied with evidence-based, print or web-based information to take home. HCP wanted access to similar material to assist in their risk discussions with women, as well as professionally endorsed multi-disciplinary education for their own learning. HCP including midwives emphasised all HCP shared responsibility for women's post-HDP follow-up: "It's everyone's business… if you have that opportunity, you find out that someone's got that history, you say, 'Oh, did you know? Has anyone spoken to you about this?" (Midwife). Both women and HCP favoured more structured long-term follow-up to facilitate the transition from hospital to community health. Conclusion: Women and HCP wanted more, easily accessible information about post-HDP health, as well as a more structured transition from hospital to community health post-HDP. This evidence will guide development of post-HDP education.